2020
DOI: 10.1007/s12529-020-09859-8
|View full text |Cite
|
Sign up to set email alerts
|

Social Psychological Predictors of Sleep Hygiene Behaviors in Australian and Hong Kong University Students

Abstract: Social psychological predictors of sleep hygiene behaviors in Australian and Hong Kong university students AbstractBackground. Sleep hygiene behaviors in undergraduate students are associated with night-time sleep duration and quality, fatigue, daytime sleepiness, and psychological distress. This study aimed to identify the social psychological factors that impact on university students' sleep hygiene behaviors in samples from two countries. Methods. Participants were undergraduate students from Australia (N=2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(11 citation statements)
references
References 55 publications
(75 reference statements)
0
9
0
Order By: Relevance
“…Maintenance self-efficacy, on the other hand, is an optimistic belief during the post-actional (volitional) phase, where an individual perceives they have the competence and capability to persevere the formed action of behavior in the face of obstacles. A recent meta-analysis provided support for the HAPA constructs of planning and self-efficacy in predicting health behaviors [44], and previous research has also shown planning and self-efficacy to predict college students' hand washing [45,46] and sleep hygiene [47] more specifically.…”
Section: Introductionmentioning
confidence: 93%
“…Maintenance self-efficacy, on the other hand, is an optimistic belief during the post-actional (volitional) phase, where an individual perceives they have the competence and capability to persevere the formed action of behavior in the face of obstacles. A recent meta-analysis provided support for the HAPA constructs of planning and self-efficacy in predicting health behaviors [44], and previous research has also shown planning and self-efficacy to predict college students' hand washing [45,46] and sleep hygiene [47] more specifically.…”
Section: Introductionmentioning
confidence: 93%
“…However, the application of the TPB in the study of sleep behavior is surprisingly rare and focusses on student samples. A recent review [15] identified six studies using the TPB measuring actual behavioral outcomes beyond intention in the areas of sleep hygiene, sleep duration, or sleep patterns, and an additional study was published afterwards [19]. Knowlden et al [20] reported that attitude, subjective norm, and PBC explained 36% of variance in behavioral intention to get enough sleep, and PBC and intention explained 34% of variance in self-reported last night's sleep duration among US American students.…”
Section: Introductionmentioning
confidence: 99%
“…Intention, PBC, coping and action planning together accounted for 60% of variance in sleep hygiene behavior, which, in turn, explained about 8% of variance in sleep quality. The most recent prospective study [19] on sleep hygiene in Australian and Hong Kong university students pointed out that TPB models including action planning explained 52% (Australia) and 48% (Hong Kong) of variance in sleep hygiene behavior assessed 4 weeks after a baseline questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…One emerging line of investigation is in the use of integrated models of behavior (for an overview see [ 14 ]). Studies investigating a range of behaviors have shown support for such models in explaining and predicting individuals’ intentions and behavior [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. These integrated social cognition models are often coined hybrid models, as they draw constructs and specified relations from more than one existing theory to arrive at a new theory or a more comprehensive model.…”
Section: Introductionmentioning
confidence: 99%